Bio-accumulation effects of heavy metals Pb, Zn and Cd on Procecidochares utilis parasitism to Eupatorium adenophorum at Suzu metal mines, Yunnan. Issue 9 (September 2022) - Lan, Mingxian; Zeng, Shuquan; Hussain, Mehboob; Tang, Ping; Ma, Sha; Yi, Jing; Li, Lifang; Wang, Jixiu; Guo, Jianfang; Wu, Guoxing; Gao, Xi
Abstract: Procecidochares utilis is an obligatory parasitic insect to Eupatorium adenophorum . Both organisms have been spread to some metal mines areas. The objective of this study is to comprehend the trend of heavy metals transfer and the process of their bio-accumulation in the soil- E. adenophorum - P. utilis system and particularly their impact on the parasitic effect of P. utilis to E. adenophorum to reflect the impact of heavy metals on obligate parasitic insect and its host. Therefore, a detailed investigation was carried out at the Suzu Lead–Zinc Mine in Yunnan Province using the concentric circle's method. The results showed that the parasitic rate of P. utilis to a single plant and branch is positively correlated with distance. The metals content of the soil in E. adenophorum and P. utilis, decreased dramatically with an increase in distance away from the center of the mining area. From which is cleared that these metals could enter to E. adenophorum and P. utilis through the soil- E. adenophorum - P. utilis system which likely to affect its parasitic activities. In addition, the parasitic rate is impacted by per Zn content greatly, and the parasitic rate per plant is affected by Cd content enormously. This work could provide important basis of data for further understanding and clarifying the effects of bioaccumulation and heavy metals pollution on various aspects of the food chain. Simultaneously, it could clarify and simplify whether heavy metal contamination affects the parasitic behaviour of some obligatory parasitic insects. Graphical abstract: Abstract : Heavy metals; Eupatorium adenophorum ; Procecidochares utilis ; Obligate parasitism. Highlights: Concentric circles method was used to assess heavy metals accumulation. Heavy metals pollution in mining area reduced the amount of Procecidochares utilis . The content of heavy metals uptrend alongside drawing closer to mine center. The parasitic rate is positively correlated with the distance from mine center. Metals bioaccumulation lowered parasitic effect of P. utilis on Crofton weed.